Randomized Phase III Postoperative Trial of Platinum-Based Chemotherapy Versus Capecitabine in Patients With Residual Triple-Negative Breast Cancer Following Neoadjuvant Chemotherapy: ECOG-ACRIN EA1131. Issue 23 (10th August 2021) - Mayer, Ingrid A.; Zhao, Fengmin; Arteaga, Carlos L.; Symmans, William F.; Park, Ben H.; Burnette, Brian L.; Tevaarwerk, Amye J.; Garcia, Sofia F.; Smith, Karen L.; Makower, Della F.; Block, Margaret; Morley, Kimberly A.; et al.
Abstract : PURPOSE: Patients with triple-negative breast cancer (TNBC) and residual invasive disease (RD) after completion of neoadjuvant chemotherapy (NAC) have a high-risk for recurrence, which is reduced by adjuvant capecitabine. Preclinical models support the use of platinum agents in the TNBC basal subtype. The EA1131 trial hypothesized that invasive disease-free survival (iDFS) would not be inferior but improved in patients with basal subtype TNBC treated with adjuvant platinum compared with capecitabine. PATIENTS AND METHODS: Patients with clinical stage II or III TNBC with ≥ 1 cm RD in the breast post-NAC were randomly assigned to receive platinum (carboplatin or cisplatin) once every 3 weeks for four cycles or capecitabine 14 out of 21 days every 3 weeks for six cycles. TNBC subtype (basal v nonbasal) was determined by PAM50 in the residual disease. A noninferiority design with superiority alternative was chosen, assuming a 4-year iDFS of 67% with capecitabine. RESULTS: Four hundred ten of planned 775 participants were randomly assigned to platinum or capecitabine between 2015 and 2021. After median follow-up of 20 months and 120 iDFS events (61% of full information) in the 308 (78%) patients with basal subtype TNBC, the 3-year iDFS for platinum was 42% (95% CI, 30 to 53) versus 49% (95% CI, 39 to 59) for capecitabine. Grade 3 and 4 toxicities were more common with platinum agents. The Data and Safety Monitoring Committee recommended stopping the trial as it was unlikely that further follow-up would show noninferiority or superiority of platinum. CONCLUSION: Platinum agents do not improve outcomes in patients with basal subtype TNBC RD post-NAC and are associated with more severe toxicity when compared with capecitabine. Participants had a lower than expected 3-year iDFS regardless of study treatment, highlighting the need for better therapies in this high-risk population.